2013
DOI: 10.1044/1092-4388(2012/12-0099)
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Constraints on Children's Overt Marking of BE by Dialect and Age

Abstract: Purpose Overt marking of BE in nonmainstream adult dialects of English is influenced by a number of linguistic constraints, including the structure's person, number, tense, contractibility, and grammatical function. In the current study, we examined the effects of these constraints on overt marking of BE in children as a function of their nonmainstream English dialect and age. Methods The data were language samples from 62 children, aged four to six years; 24 spoke African American English (AAE) and 38 spoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
3
17
1
Order By: Relevance
“…Given the larger number of productions for contractible contexts, it is interesting that all children showed variable marking of auxiliary is/are in contractible contexts in post-treatment samples, averaging 44% for all children. This is consistent with the variable marking in the study by Roy et al (2013) who found an average 57% marking rate of contractible contexts in typically developing AAE speaking children.…”
Section: Linguistic Influence: Contractibility Of Auxiliary Is/aresupporting
confidence: 92%
See 3 more Smart Citations
“…Given the larger number of productions for contractible contexts, it is interesting that all children showed variable marking of auxiliary is/are in contractible contexts in post-treatment samples, averaging 44% for all children. This is consistent with the variable marking in the study by Roy et al (2013) who found an average 57% marking rate of contractible contexts in typically developing AAE speaking children.…”
Section: Linguistic Influence: Contractibility Of Auxiliary Is/aresupporting
confidence: 92%
“…When coding for contractibility, coding was conducted in keeping with the work by Roy et al (2013). The context was coded as either contractible or uncontractible based on whether or not the form could be contracted, regardless of whether or not it was actually contracted in the utterance.…”
Section: Data: Coding Of Child Utterancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Using forms of be as an example, these marking options include mainstream overt expressions (i.e., I am, you are, she is, I was, they were), nonmainstream overt expressions (i.e., they is, we was), and nonmainstream zero expressions (e.g., he Ø, you Ø). In the AAE and SWE varieties studied here, and as shown by the examples, the nonmainstream overt expressions are limited to are and were contexts, and the nonmainstream zero marked expressions are limited to is and are contexts (Roy, Oetting, & Moland, 2013). 1 On the basis of these findings, AAE and SWE can be described as presenting structural overlap that makes it impossible to determine if utterances such as They was driving or You Ø coming with me were produced by an AAE or SWE speaker.…”
Section: Structural Overlap Between Aae Swe and The Grammatical Conmentioning
confidence: 73%